The effect of water cement ratio (WCR) on compressive strength of interlocking bricks with mix design variations. Issue 1 (September 2020) - Malahayati, N; Hayati, Y; Mahlil; Sundary, D; Maulina, F
Abstract: Interlocking brick is a material used for wall work in home construction. Called Interlocking Brick or Brick Interlock because the method of arranging the bricks is interlocked with one another. This interlocking brick itself began to be known in Aceh Province after the 2004 tsunami disaster. Interlocking brick is a block of compacted soil, made of cement, silt soil, and dried sand, measuring 300 χ 150 χ 100 cm 3 . Interlocking brick can function as a wall that can withstand structural and non-structural components. The purpose of this research is to get the compressive strength value of interlocking bricks designed with variations in the water cement ratio (WCR) so that the optimum compressive strength of interlocking bricks is obtained. The WCR used was 0.3; 0.4; and 0.5, while for the composition of cement, silt, and sand the ratio of 1:2:2 is used. The making of test specimens for testing the compressive strength of interlocking bricks is by cutting the interlocking bricks into cubes measuring 50 χ 50 χ 50 mm by 5 specimens for each variation so that the total of the total specimens are 45 specimens. Testing is done at the age of 7, 14, and 28 days. The results of the compressive strength of interlocking bricks using WCR 0.3 average compressive strength at the age of 7 days reached 8.10 MPa, 14 days reached 9.49 MPa and 28 days reached 10.94 MPa. For WCR 0.4, compressive strength on average at 7 days reaches 5.69 MPa, 14 days reaches 7.61 MPa and 28 days reaches 9.77 MPa. And for WCR 0.5 the average compressive strength at the age of 7 days reaches 5.36 MPa, 14 days reaches 8.25 MPa and 28 days reaches 9.93 MPa. From the compressive strength test results the interlocking brick with a WCR variation of 0.3; 0.4; and 0.5 with a mixture of 1:2:2 can be used as wall work material in house construction for structural construction and the optimum compressive strength value is obtained at WCR 0.3.